معوقات تنمية ذوي الاعاقة وأثرها على الهوية في التعليم ما بعد الثانوي من وجهة نظر أساتذة التربية الخاصة في جامعة حائل - هيا مروح خلف السرديه (Scientific Journal of University of Benghazi, 2018)
The aim of this study is to investigate the opinions of professors that are working at Hail University in Saudi Arabia about Barriers of the development of individuals with special needs and its impact on the identity in post-secondary education. To achieve the goal of the study, used the descriptive approach.. the results after analyzing the questionnaire. The average is very high, which indicates the importance of the for items in the developing and improving the disabled ID, trends and situation got the highest average, then the physical aspect, ID developing, and the accessibility got the lowest average (3.8), The recommendations are: Positive trends about the disabled, and changing the negative trends.